DAMPAK PENERBITAN SUN DOMESTIK TERHADAP PERKEMBANGAN SEKTOR PERBANKAN - G.A. Diah Utari; Ina Nurmalia Kurniati; Ndari Surjaningsih (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2011)
This study examines the impact of public sector credit in the form of goverment domestic bond (hereinafter is called SUN Domestic = Surat Utang Negara Domestik) to the development of financial sector especially banking sector. We use Vector Error Correction Method and Panel Data Method for monthly data from period of 2003 to 2009. The study found that the existence SUN domestic have significant impact to the development of banking sector that is represented by the ratio of total credit to GDP and ratio of credit to private sector to GDP. The increase of composition of SUN domestic in the bank’s aset portfolio relative to total credit has negative impact to bank’s lending. Therefore there might be optimal composition of the amount of SUN domestic in bank's aset portfolio that wouldn’t have negative impact to bank’s credit. Empirical result using panel data shows that ownership of SUN domestic in bank's asets portofolio, increases bank's profit and efficiency. Klasifikasi JEL: G21, H6, H63